Intravenous gammaglobulin treatment in multiple sclerosis and experimental autoimmune encephalomyelitis: delineation of usage and mode of action. (November 1994) - Achiron, A; Gilad, R; Margalit, R; Gabbay, U; Sarova-Pinhas, I; Cohen, I R; Melamed, E; Lider, O; Noy, S; Ziv, I
Abstract : Multiple sclerosis (MS) is a central nervous system demyelinating disease of implicated autoimmune aetiology. The effect was evaluated of intravenous gammaglobulin (IVIg), a successful therapy in various autoimmune diseases, in relapsing-remitting MS patients treated for three years. IVIg treatment significantly reduced the number and severity of acute exacerbations and resulted in a lesser neurological disability. There were no significant short or long-term adverse effects to IVIg treatment. To clarify the putative therapeutic effects of IVIg, this treatment was examined in the animal model of experimental autoimmune encephalomyelitis (EAE) in the rat. IVIg suppressed active EAE in relation to disease severity and duration, despite the presence of T-cell reactivity to specific antigens, while the treatment had no effect on passive EAE induced by adoptive transfer of myelin basic protein specific CD4 + T-cells. It is concluded that IVIg treatment may be a promising treatment in relapsing-remitting MS as it can alter the natural course of the disease.